2014
DOI: 10.1208/s12248-014-9648-x
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-mechanistic Model for the Effects of a Novel Glucagon Receptor Antagonist on Glucagon and the Interaction Between Glucose, Glucagon, and Insulin Applied to Adaptive Phase II Design

Abstract: Abstract. A potent novel compound (MK-3577) was developed for the treatment of type 2 diabetes mellitus (T2DM) through blocking the glucagon receptor. A semi-mechanistic model was developed to describe the drug effect on glucagon and the interaction between glucagon, insulin, and glucose in healthy subjects (N=36) during a glucagon challenge study in which glucagon, octreotide (Sandostatin), and basal insulin were infused for 2 h starting from 3, 12, or 24 h postdose of a single 0-900 mg MK-3577 administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…13 The ability of insulin to suppress the glycogenolytic response to glucagon at high insulin concentration is not reflected in previously published models of glucose-glucagon dynamics. [18][19][20] A comparative study found that a multiplicative relationship was needed to describe insulin's inhibitory effect and glucagon's stimulating effect on glycogenolysis with insulin overriding the effect of glucagon at high concentrations of both hormones. 21 Recently, we extended the multiplicative model by incorporating the interaction between insulin and glucagon on glycogenolysis.…”
mentioning
confidence: 99%
“…13 The ability of insulin to suppress the glycogenolytic response to glucagon at high insulin concentration is not reflected in previously published models of glucose-glucagon dynamics. [18][19][20] A comparative study found that a multiplicative relationship was needed to describe insulin's inhibitory effect and glucagon's stimulating effect on glycogenolysis with insulin overriding the effect of glucagon at high concentrations of both hormones. 21 Recently, we extended the multiplicative model by incorporating the interaction between insulin and glucagon on glycogenolysis.…”
mentioning
confidence: 99%
“…The blocking effect of REGN1193 was evident as early as 6 h post‐dose and persisted for at least 3 weeks. Previous work with the small molecule MK‐0893 demonstrated predictable glucose‐lowering in subjects with diabetes based on the degree of inhibition of glucagon‐mediated hyperglycaemia; however, it is essential that the effects of REGN1193 be tested in subjects with type 2 diabetes to estimate clinical effects and allow comparison with the ≥1% glycated haemoglobin (HbA1c) reductions observed with the small molecule antagonists and antisense molecules…”
Section: Summary Of Glucagon Receptor Blocking Drugs Evaluated In Humansmentioning
confidence: 99%
“…Peng et al [9] proposed a detailed model for the glucagon challenge test intended to study the effect of a glucagon receptor antagonist drug on glucose homeostasis in healthy and T2DM subjects. Their focus was to incorporate the PK characteristics of the drug into the model.…”
Section: Introductionmentioning
confidence: 99%